What makes growth oriented small scale companies innovative? : a look at absorptive capacities. - Chua , Beng Hui; Idris, Khairuddin (2009)
The purpose of this study is to present the concept of the firm’s absorptive capacity as a multidimensional, dynamic construct to test the relationship with innovative capabilities in the context of growthoriented companies. The study draws on empirical results from 215 MSC status companies. The hypotheses were tested using hierarchical regression analysis. Using two separate instruments to measure independent variable: absorptive capacity, and dependent variable: innovative capabilities. The results of the empirical tests give some support to the view that the flow of knowledge is crucial for sustaining innovative capabilities. The regression estimation shows that knowledge acquisition, knowledge dissemination and knowledge utilization were significantly reflected in the firm’s innovative capabilities. The finding of this study shed some light on the importance of the firm’s ability to acquire, disseminate and utilize knowledge effectively in order to achieve higher innovation.